Pengaruh Kompos Limbah Sagu Terhadap Pertumbuhan Tanaman Kelapa Sawit Elaeis Guineensis Jacq.) Di Pembibitan Utama - 1Ikhsan ' Syahtria; Sampoerno ' '; Wardati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims for knowing the influence a giving of oil palm seeds in the results of giving sago waste compost in main nursery. The researched was carried out at Faculty of Agricultural experiment station, UR in October 2015 – January 2016 using a randomized etely design which consist of six treatments and four replications that is 0 g/plant; 50 g/plant; 100g/plant; 150g/plant; 200 g/plant; 250 g/plant. The results of research shows that the application of sago waste compost significant effect on all parameters of observation. As for the plant height, number of leaves, diameter hump and dry weight has best value in treatment 200 g/plant. While for the root volume parameter has best value in treatment 250 g/plant. Keywords : Sago waste compost, main nursery and oil palm